The Peran Perpustakaan PTKI terhadap Literasi Digital : Kajian dalam Mendukung Program Sustainable Development Goal (SDG 4) Pendidikan Berkualitas: Peran Perpustakaan PTKI terhadap Literasi Digital : Kajian dalam Mendukung Program Sustainable Development Goal (SDG 4) Pendidikan Berkualitas - Mega Alif Marintan; Khoirul Maslahah; Nushrotul Hasanah Rahmawati; Imam Mahmudi; Nur Husniyatul Adyani (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Islamic Religious Colleges (PTKI) are educational institutions that focus on character building and religious understanding. UIN Raden Mas Said Surakarta is required to integrate digital literacy into its educational curriculum. This study aims to explore the programs and strategies implemented by the PTKI library at UIN Raden Mas Said Surakarta to improve digital literacy. It employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation.The results indicate that the library contributes to the enhancement of digital literacy in alignment with SDG 4, namely quality education, through lifelong learning, quality improvement, and accessibility and inclusivity. Lifelong learning is supported through the utilization of artificial intelligence-based technologies as a strategic effort to strengthen access to learning. The improvement in learning quality is achieved through the provision of relevant collections in both physical and digital formats. Accessibility and inclusivity are promoted through efforts to create an inclusive learning environment, including the development of disability-friendly facilities and collaboration with the Disability Services Center (PSLD) at UIN Raden Mas Said Surakarta. In conclusion, the PTKI library plays a crucial role in supporting digital literacy by integrating technological innovation, resource development, and inclusive practices into its services.